2019
DOI: 10.1111/cen.14076
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in Turner syndrome: Karyotype does not predict ovarian response to stimulation

Abstract: Objective Turner syndrome (TS) is responsible for gonadal dysgenesis with high risk of premature ovarian insufficiency. Little is known about fertility preservation (FP) strategies is this population. Design Data from women with TS consulting with a fertility specialist in our FP centre from 2014 to 2018 were retrospectively collected. Measurement Total number of mature oocytes cryopreserved using vitrification. Patients Nine women with TS were referred. Three women with different karyotypes underwent controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…Over the past few years, several studies reported that follicles were found in girls with a 45,X karyotype (13,19). In addition, pregnancies were described in women with a complete monosomy of the X chromosome in extraovarian cells (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, several studies reported that follicles were found in girls with a 45,X karyotype (13,19). In addition, pregnancies were described in women with a complete monosomy of the X chromosome in extraovarian cells (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Experience with this method in Turner syndrome is already available. 8,[20][21][22] It should be noted, however, that the anatomical conditions for cryopreservation of oocytes (vaginal sonography) must be F I G U R E 1 Recommendation for fertility protection in women with Turner syndrome, based on genotype, ovarian reserve, and health of the woman. AMH, anti-Müllerian hormone [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Cryopreservation Of Oocytesmentioning
confidence: 99%
“…Experience with this method in Turner syndrome is already available 8,20‐22 . It should be noted, however, that the anatomical conditions for cryopreservation of oocytes (vaginal sonography) must be given for the mostly still young women.…”
Section: Fertility Preservation Techniques In Women With Turner Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…52 However, spontaneous puberty and menarche has been reported in children with monosomy 45,X. 53,54 Oocyte cryopreservation has become an established component of assisted reproductive technology, allowing women of reproductive age to preserve their oocytes for future use. There have been a handful of published case reports and studies documenting successful oocyte cryopreservation in TS individuals.…”
Section: Turner's Syndromementioning
confidence: 99%